AKSI KASIH NATAL 2025KEPADA ANAK PANTI ASUHAN RAHPIA DAN CLARESTA KOTA MEDAN SEBAGAI WUJUD AKTUALISASI KASIH KRISTUS - Benny Andreson Situmorang; Dina Br Sembiring (JOURNAL OF COMMUNITY DEDICATION, 2025)
Love is a feeling that exists within humans, because humans are created in the image and likeness of God because God is love, this feeling will arise if humans have a sense of belonging and love. The true meaning of love is when we give the best to other people, whether that means making others happy and being willing to make sacrifices like God's perfect love which loves everyone, God's love which is an example for everyone so that in the first letter of John it says that we love because God first loved (1 John 4:19).